Renal replacement therapy as bridging-to-recovery in refractory hepatorenal syndrome - Luedemann, Christoph; Plota, Jessica; Nattermann, Jacob; Strassburg, Christian P.; Lutz, Philipp; Goeser, Felix (Zeitschrift für Gastroenterologie, 2021)
A 50-year-old female patient with cirrhosis due to alcoholic steatohepatitis was referred to our department because of recurrent hepatorenal syndrome (HRS) and hepatic hydrothorax. Clinically, severe anasarca was the leading problem. In contrast to previous episodes, HRS did not respond to standard treatment including terlipressin.Given the severe, refractory hyperhydration, we finally initiated renal replacement therapy (RRT). Subsequently, RRT was performed without severe side effects for more than 100 days. In the meantime, liver function remarkably improved, most probably due to the prolonged abstinence from alcohol. Finally, RRT could be stopped. Since then, our patient has remained in good clinical condition for more than 6 months, with well-compensated Child-Pugh stage A cirrhosis and only mild chronic kidney disease stage III.In conclusion, this case highlights that RRT may be considered in individual cases as bridging therapy in refractory HRS until the liver regenerates due to the absence of damaging mechanisms.
Keywords: hepatorenal syndrome; renal replacement therapy; liver cirrhosis; alcoholic steatohepatitis